Smart Bus System & Bus Tracking for UTHM Pagoh Residential Students - Khairunnajlaa Zamri,; Ahmad, Nur Azliza; A. Fahmi Iman N. Fadzil, (Multidisciplinary Applied Research and Innovation, 2025)
To ensure that students can travel between college and campus comfortably, students can use the bus system and the tracking system. Travel is made easier with system security measures and information updates. For example, the bus tracking system uses NEO 6M GPS and ESP 32 to provide real-time updates via Telegram, to inform students of bus location and arrival time. Information system with LCD display that displays travel routes and other updates. Furthermore, the security system uses RFID for UTHM student ID authentication using the student matrix card and a motion sensor (PIR) to detect any movement after the bus door is closed. This project aims to develop a Smart Bus system that combines these qualities to deliver accurate location data as well as safe transit. Two main systems have been built, one for user safety using RFID and PIR, and one for information with LCD display and GPS. This integrated solution simplifies and improves transportation for UTHM students and it can also be used in the workplace.